1993
DOI: 10.1007/bf02244941
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nicotine patch and nicotine gum as individual versus combined treatments for tobacco withdrawal symptoms

Abstract: Nicotine gum and transdermal nicotine have been shown to relieve withdrawal and double success rates over placebo in trials of smoking cessation. This study tested whether combining the two methods would relieve withdrawal more effectively compared to either treatment alone. Twenty-eight smokers served as their own controls in each of four conditions: active gum + active patch (double active), active gum + placebo patch (gum only active), placebo gum + active patch (patch active) and placebo gum + placebo patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
6
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(91 citation statements)
references
References 17 publications
9
73
6
3
Order By: Relevance
“…replacing only a part of the nicotine taken in from smoking, is very common. A method to ameliorate the underdosing has been to combine several NR products, most commonly as patch plus gum [15,16]. There is evidence from a meta-analysis that combining a nicotine patch with an oral form of NR was more effective than a single type of NR [3].…”
Section: Indications For Nrcontrasting
confidence: 40%
“…replacing only a part of the nicotine taken in from smoking, is very common. A method to ameliorate the underdosing has been to combine several NR products, most commonly as patch plus gum [15,16]. There is evidence from a meta-analysis that combining a nicotine patch with an oral form of NR was more effective than a single type of NR [3].…”
Section: Indications For Nrcontrasting
confidence: 40%
“…This approach is therefore not a feasible way to increase abstinence rates beyond those observed in this study. Therefore, the present focus on the combined use of different nicotine treatments and dosage patterns during therapy is a worthwhile approach [13][14][15]. The transdermal route is a fixed dose system with a low frequency of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Killen et al (2001) recently reported that nicotine replacement therapy fails to attenuate withdrawal symptoms in adolescents, findings that contrast with reports of the effectiveness of these treatment approaches in adults (Rose et al, 1985;Fagerstrom et al, 1993).…”
mentioning
confidence: 86%